Systematic study of a thulium-doped all-polarization maintaining modelocked fiber laser from a low to high fundamental repetition rate - Cuadrado-Laborde, Christian (2025)
Fil: Cuadrado-Laborde, Christian. Universidad de Valencia. Departamento de Física Aplicada y Electromagnetismo; España